Effects of salinity on the immune response of an ‘osmotic generalist’ bird - Sánchez Gutiérrez, Jorge; Abad Gómez-Pantoja, José María; Villegas Sánchez, María Auxiliadora; Sánchez Guzmán, Juan Manuel; Masero Osorio, José Antonio (Oecologia, 2013)
Salt stress can suppress the immune function of fish and other aquatic animals, but such an effect has not yet been examined in air-breathing vertebrates that frequently cope with waters (and prey) of contrasting salinities. We investigated the effects of seawater salinity on the strength and cost of mounting an immune response in the dunlin Calidris alpina, a long-distance migratory shorebird that shifts seasonally from freshwater environments during the breeding season to marine environments during migration and the winter period. Phytohaemagglutinin (PHA)-induced skin swelling, basal metabolic rate (BMR), body mass, fat stores, and plasma ions were measured in dunlins acclimated to either freshwater or seawater (salinity: 0.3 and 35.0%, respectively). Seawater-acclimated dunlins mounted a PHA-induced swelling response that was up to 56% weaker than those held under freshwater conditions, despite ad libitum access to food. Freshwater-acclimated dunlins significantly increased their relative BMR 48 h after PHA injection, whereas seawater acclimated dunlins did not. However, this differential immune and metabolic response between freshwater- and seawater-acclimated dunlins was not associated with significant changes in body mass, fat stores or plasma ions. Our results indicate that the strength of the immune response of this small-sized migratory shorebird was negatively influenced by the salinity of marine habitats. Further, these findings suggest that the reduced immune response observed under saline conditions might not be caused by an energy or nutrient limitation, and raise questions about the role of osmoregulatory hormones in the modulation of the immune system. Project CGL2011-27485 (Spanish Ministry of Science and Innovation) and a grant to J.S.G. from Junta of Extremadura provided financial support for this study. peerReviewed